Binder for electrode of lithium secondary battery, binder composition for electrode, negative electrode, and lithium secondary battery
By using a polyurethane aqueous dispersion containing specific polyisocyanate, hydrogenated polybutadiene polyol and sodium carboxylate salt as the electrode adhesive for lithium secondary batteries, the electrode expansion problem caused by charging and discharging is solved, and more stable battery performance and lower gas generation are achieved.
Patent Information
- Application Number
- CN202380052575.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-14
- Filing Date
- 2023-06-19
- Publication Date
- 2025-02-25
AI Technical Summary
The negative electrode of the lithium secondary battery deteriorates performance due to expansion during charging and discharging, and the prior art fails to effectively reduce the expansion of the electrode caused by charging and discharging.
As the binder for electrodes, a sodium salt of polyurethane obtained by reacting an aliphatic polyisocyanate, a hydrogenated polybutadiene polyol, a carboxylic acid with an active hydrogen group, a sodium salt thereof, and a chain extender.
The electrode expansion caused by charging and discharging is effectively reduced, the performance stability of the lithium secondary battery is improved, and the generation of gas during charging and discharging is suppressed.
Smart Images

Figure BDA0005232903280000201 
Figure BDA0005232903280000241
Abstract
Description
Technical Field
[0001] Embodiments of the present invention relate to a binder for a lithium secondary battery electrode, a binder composition for an electrode, a negative electrode, and a lithium secondary battery. Background Art
[0002] Lithium secondary batteries, also known as lithium-ion secondary batteries, are high-voltage, high-energy-density storage devices used, for example, in driving power supplies for electronic devices. The electrodes of lithium secondary batteries are usually manufactured by applying a mixture of an electrode active material, a conductive agent, and a binder to the surface of a current collector and drying it. The binder is used to impart adhesion between the electrode active material and the current collector. Therefore, the binder has a great influence on the characteristics of lithium secondary batteries.
[0003] As an adhesive for electrodes of lithium secondary batteries, Patent Document 1 discloses an adhesive containing a polyurethane aqueous dispersion, wherein the polyurethane contains: a polyisocyanate, an olefin polyol, a compound having one or more active hydrogen groups and a hydrophilic group, and a chain extender. In addition, it is disclosed that one or more selected from polybutadiene polyol, polyisoprene polyol, hydrogenated polybutadiene polyol and hydrogenated polyisoprene polyol are used as the olefin polyol. Furthermore, it is disclosed that a carboxylic acid-containing compound and a salt thereof are used as a compound having an active hydrogen group and a hydrophilic group.
[0004] Patent Document 2 discloses an electrode binder composition that can obtain an electrode that exhibits high durability even when using an active material with a large volume change, and uses a fibrous nano carbon material together with polyurethane. In addition, as the polyurethane, it is disclosed that a polyurethane obtained by reacting polyisocyanates, polyols, compounds with one or more active hydrogen groups and hydrophilic groups, and chain extenders is used. Furthermore, it is disclosed that one or more selected from polybutadiene polyols, polyisoprene polyols, hydrogenated polybutadiene polyols, and hydrogenated polyisoprene polyols are used as the polyol. In addition, it is disclosed that a carboxylic acid-containing compound and its salt are used as a compound with an active hydrogen group and a hydrophilic group.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2015 / 019598
[0008] Patent Document 2: International Publication No. 2020 / 217730 Summary of the invention
[0009] Technical problem that the invention aims to solve
[0010] For example, when the negative electrode active material contains SiO, the electrode expands due to charge and discharge, and the performance of the lithium secondary battery deteriorates. Therefore, it is required to reduce the expansion of the electrode caused by charge and discharge.
[0011] Patent Documents 1 and 2 disclose that, in polyurethane used as an adhesive, polybutadiene polyol and polyisoprene polyol may be used together with their hydrogenated products as polyols, and carboxylic acid-containing compounds and their salts may be used as compounds having an active hydrogen group and a hydrophilic group. However, there is no disclosure of a combination of hydrogenated polybutadiene polyol and a sodium salt of a carboxylic acid, nor is there any disclosure that the combination can reduce electrode expansion caused by charge and discharge.
[0012] An object of an embodiment of the present invention is to provide a binder for lithium secondary battery electrodes that can reduce electrode expansion caused by charge and discharge.
[0013] Technical solutions to the problem
[0014] The present invention includes the following embodiments.
[0015] [1] A binder for lithium secondary battery electrodes, comprising an aqueous dispersion of a sodium salt of a polyurethane obtained by reacting (A) at least one of an aliphatic polyisocyanate and an alicyclic polyisocyanate, (B) a hydrogenated polybutadiene polyol, (C) a carboxylic acid having one or more active hydrogen groups, and (D) a chain extender.
[0016] [2] The electrode binder according to [1], which is used for a negative electrode of a lithium secondary battery, wherein the negative electrode contains SiO as a negative electrode active material.
[0017] [3] A binder composition for an electrode of a lithium secondary battery, comprising: a sodium salt of a polyurethane obtained by reacting (A) at least one of an aliphatic polyisocyanate and an alicyclic polyisocyanate, (B) a hydrogenated polybutadiene polyol, (C) a carboxylic acid having one or more active hydrogen groups, and (D) a chain extender; a conductive agent; and water.
[0018] [4] The binder composition for an electrode according to [3], wherein the conductive agent contains fibrous nanocarbon.
[0019] [5] A negative electrode for a lithium secondary battery, comprising: a solid component of the electrode binder according to [1] or [2] or the electrode binder composition according to [3] or [4]; and a negative electrode active material containing SiO.
[0020] [6] The negative electrode according to [5], comprising fibrous nanocarbon as a conductive agent.
[0021] [7] A lithium secondary battery comprising the negative electrode described in [5] or [6].
[0022] Effects of the Invention
[0023] According to the embodiment of the present invention, electrode expansion caused by charge and discharge can be reduced. DETAILED DESCRIPTION
[0024] The binder for electrodes of the lithium secondary battery of the present embodiment includes an aqueous dispersion of a sodium salt of a polyurethane (hereinafter sometimes referred to as "polyurethane") obtained by reacting at least one of an aliphatic polyisocyanate and an alicyclic polyisocyanate as component (A), a hydrogenated polybutadiene polyol as component (B), a carboxylic acid having one or more active hydrogen groups as component (C), and a chain extender as component (D).
[0025] Generally, when the electrode active material includes SiO, the electrode expands due to the charge and discharge of the lithium secondary battery. In contrast, if the electrode binder involved in this embodiment, even when the electrode active material includes SiO, the electrode expansion can be reduced. In addition, when the electrode active material includes SiO, if the carboxyl group from the above-mentioned carboxylic acid is an amine salt, gas is easily generated. In contrast, by making the carboxyl group a sodium salt, the generation of gas can be suppressed.
[0026] [(A) At least one of an aliphatic polyisocyanate and an alicyclic polyisocyanate]
[0027] In the present embodiment, (A) aliphatic polyisocyanate and / or alicyclic polyisocyanate is used as the polyisocyanate.
[0028] Examples of the aliphatic polyisocyanate include tetramethylene diisocyanate, dodecamethylene diisocyanate, hexamethylene diisocyanate (HDI), 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, lysine diisocyanate, 2-methylpentane-1,5-diisocyanate, and 3-methylpentane-1,5-diisocyanate. These may be used alone or in combination of two or more.
[0029] Examples of the alicyclic polyisocyanate include isophorone diisocyanate (IPDI), dicyclohexylmethane 4,4'-diisocyanate (hydrogenated MDI), hydrogenated xylylene diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate, and 1,3-bis(isocyanatemethyl)cyclohexane. These may be used alone or in combination of two or more.
[0030] The amount of the component (A) is not particularly limited, and may be, for example, 5% by mass to 40% by mass, or 10% by mass to 30% by mass, relative to 100% by mass of the polyurethane.
[0031] [(B) Hydrogenated polybutadiene polyol]
[0032] In the present embodiment, (B) hydrogenated polybutadiene polyol is used as the polyol. By combining the above-mentioned sodium salt of carboxylic acid with hydrogenated polybutadiene polyol, electrode expansion after charge and discharge can be reduced.
[0033] As the hydrogenated polybutadiene polyol, it is preferred to use a hydrogenated polybutadiene polyol having an average of 1.3 or more hydroxyl groups per molecule, more preferably a hydrogenated polybutadiene polyol having an average of 1.5 to 2.5 hydroxyl groups, and still more preferably a hydrogenated polybutadiene polyol having an average of 1.7 to 2.2 hydroxyl groups. In this specification, the number of hydroxyl groups (number of functional groups) per molecule is a value calculated by the following formula.
[0034] Number of functional groups = {(hydroxyl value) × (Mn)} / (56.1 × 1000)
[0035] As the hydrogenated polybutadiene polyol, preferably used is a hydrogenated polybutadiene polyol having a structure obtained by hydrogenating (adding hydrogen) a polybutadiene polyol having a 1,4-bonded type, a 1,2-bonded type, or a mixed polybutadiene structure in the molecule and having a hydroxyl group at the terminal. More preferably, the hydrogenated polybutadiene polyol has a structure obtained by hydrogenating a polybutadiene polyol having hydroxyl groups at both ends of the polybutadiene structure.
[0036] Hydrogenated polybutadiene polyol is a polybutadiene polyol in which a part or all of the unsaturated double bonds contained in the polybutadiene polyol are hydrogenated. The degree of hydrogenation of the hydrogenated polybutadiene polyol is not particularly limited, and for example, the iodine value may be 40 g / 100 g or less, 30 g / 100 g or less, 25 g / 100 g or less, or 15 g / 100 g or less. In this specification, the iodine value may be measured according to JIS K0070:1992.
[0037] The molecular weight of the hydrogenated polybutadiene polyol is not particularly limited. For example, the number average molecular weight (Mn) may be 600 to 10,000, 800 to 6,000, 1,000 to 5,000, or 1,200 to 4,000.
[0038] In this specification, the number average molecular weight (Mn) is a value calculated by using a calibration curve based on standard polystyrene and measured by GPC (gel permeation chromatography). Specifically, as the conditions of GPC, the column: "TSKgel Hxl" manufactured by Tosoh Corporation, mobile phase: THF (tetrahydrofuran), mobile phase flow rate: 1.0 mL / min, column temperature: 40°C, sample injection volume: 50 μL, sample concentration: 0.2 mass % can be used for measurement.
[0039] The hydroxyl value of the hydrogenated polybutadiene polyol is not particularly limited, and may be, for example, 10 to 200 mgKOH / g, 15 to 120 mgKOH / g, 20 to 100 mgKOH / g, or 50 to 90 mgKOH / g. In the present specification, the hydroxyl value may be measured according to Method A of JIS K1557-1:2007.
[0040] The amount of the hydrogenated polybutadiene polyol as the component (B) is not particularly limited, but is preferably 40 to 90% by mass, more preferably 50 to 80% by mass, based on 100% by mass of the polyurethane.
[0041] [(C) Carboxylic acid having one or more active hydrogen groups]
[0042] In the present embodiment, as a compound having an active hydrogen group, (C) a carboxylic acid having one or more active hydrogen groups is used together with (B) a hydrogenated polybutadiene polyol. (C) A carboxylic acid having one or more active hydrogen groups is a compound having one or more active hydrogen groups and a carboxyl group. The number of active hydrogen groups of the carboxylic acid may be 1 to 3, more preferably 1 or 2. An active hydrogen group refers to a group containing active hydrogen that reacts with an isocyanate group, for example, a hydroxyl group, a primary amino group (-NH2), and a secondary amino group (-NHR).
[0043] Here, the carboxyl group includes not only the acid type (-COOH) but also the salt type, i.e., the carboxylate group (-COOX. X: a cation that forms a salt with a carboxylic acid), and the acid type and the salt type can be mixed. However, in the polyurethane contained in the electrode binder or the electrode binder composition, the carboxyl group from the carboxylic acid exists in the form of a sodium salt (-COONa). Thus, even when the electrode active material contains SiO, the electrode expansion caused by charging and discharging can be reduced, and the generation of gas can be suppressed.
[0044] As carboxylic acids having one or more active hydrogen groups, for example, hydroxy acids such as dimethylolpropionic acid, dimethylolbutyric acid, dimethylolvaleric acid, dihydroxymaleic acid, dihydroxybenzoic acid, diaminobenzoic acid and their derivatives and salts thereof can be cited. As carboxylic acids having one or more active hydrogen groups, amino acids such as alanine, aminobutyric acid, aminocaproic acid, glycine, glutamic acid, aspartic acid, histidine can also be cited. Any one of them can be used, or two or more of them can be used in combination.
[0045] The carboxyl groups are neutralized to form salts, thereby making the polyurethane finally obtained water-dispersible. As a neutralizing agent at this time, sodium hydroxide is preferably used in this embodiment. Neutralization can be performed before, during or after the urethanization reaction.
[0046] The amount of the carboxylic acid having one or more active hydrogen groups as component (C) is not particularly limited, and the acid value indicating the carboxyl content in the polyurethane is preferably 5 to 50 mgKOH / g, and more preferably 5 to 45 mgKOH / g or less. By making the acid value of the polyurethane 5 mgKOH / g or more, the dispersibility in water can be improved, and by making the acid value 50 mgKOH / g or less, the electrolyte resistance can be improved. In this specification, the acid value can be calculated from the amount of KOH (mg) required to neutralize the free carboxyl groups contained in 1 g of the solid content of the polyurethane aqueous dispersion in accordance with JIS K0070-1992.
[0047] The amount of the component (C) is not particularly limited, and may be, for example, 1% by mass to 15% by mass, or 2% by mass to 10% by mass, relative to 100% by mass of the polyurethane.
[0048] [(D) Chain extender]
[0049] As the chain extender of component (D), a chain extender commonly used in the art can be used. As the chain extender, specifically, amines, i.e., diamines and polyamines are preferably used. Examples of diamines include ethylenediamine, trimethylenediamine, piperazine, isophoronediamine, etc., and examples of polyamines include diethylenetriamine, dipropylenetriamine, triethylenetetramine, etc. Any one of them can be used, or two or more of them can be used in combination.
[0050] The amount of the component (D) is not particularly limited, and may be, for example, 0.3% by mass to 10% by mass, or 0.5% by mass to 5% by mass, relative to 100% by mass of the polyurethane.
[0051] [Binder for electrodes]
[0052] The electrode binder of the present embodiment includes an aqueous dispersion of a sodium salt of a polyurethane obtained by reacting the above-mentioned components (A) to (D). That is, in the polyurethane obtained by reacting the components (A) to (D), the carboxyl group from the component (C) becomes a sodium salt and is dispersed in water. Therefore, the electrode binder includes water and a sodium salt of a polyurethane dispersed in water.
[0053] The polyurethane may be composed of only (A) component to (D) component, but as long as the effect of the present embodiment is not impaired, as polyisocyanate, polyisocyanate other than (A) component, such as aromatic polyisocyanate, aromatic aliphatic polyisocyanate, etc. In addition, as polyol, polyol other than (B) component, such as polyether polyol, polyester polyol, polycarbonate polyol, etc., may also be included, and polyols such as ethylene glycol, propylene glycol, diethylene glycol, trimethylolpropane, glycerol, etc. may also be included.
[0054] The concentration of the polyurethane in the electrode binder is not particularly limited, and may be, for example, 5% by mass to 50% by mass, or 10% by mass to 40% by mass.
[0055] The method for producing the aqueous dispersion of the sodium salt of the polyurethane is not particularly limited, and for example, the following method can be used. Component (A) is reacted with component (B) and component (C) in a solvent-free or organic solvent having no active hydrogen group to synthesize an isocyanate-terminated urethane prepolymer. At this time, component (A) is used in a stoichiometric excess of the isocyanate group to the total amount of the active hydrogen group contained in component (B) and component (C), for example, the equivalent ratio of the isocyanate group to the active hydrogen group is 1:0.85 to 0.99. After the synthesis of the above-mentioned urethane prepolymer, the carboxyl group of component (C) is neutralized with sodium hydroxide, and then dispersed and emulsified in water. Then, a chain extender (D) is added in an equivalent amount less than the residual isocyanate group (for example, the equivalent ratio of the isocyanate group to the active hydrogen group of the chain extender is 1:0.50 to 0.95), and the isocyanate group in the emulsified micelles is subjected to a surface polymerization reaction with the chain extender to form a urea bond. This increases the crosslinking density in the emulsified micelles, forming a three-dimensional crosslinked structure. Then, the used solvent is removed as necessary, thereby obtaining an aqueous dispersion of the sodium salt of polyurethane.
[0056] In the synthesis of the above-mentioned carbamate prepolymer, an organic solvent that is inactive to isocyanate groups and can dissolve the generated carbamate prepolymer can be used. As such an organic solvent, for example, dioxane, methyl ethyl ketone, acetone, dimethyl formamide, tetrahydrofuran, N-methyl-2-pyrrolidone, toluene, propylene glycol monomethyl ether acetate, etc. can be listed. In the electrode binder of the present embodiment, in the medium in which the sodium salt of polyurethane is dispersed, these organic solvents and water may be contained simultaneously, or these organic solvents may not be contained. These organic solvents are preferably finally removed.
[0057] In this embodiment, the average particle size of the aqueous dispersion of the sodium salt of polyurethane is not particularly limited, and may be, for example, in the range of 0.005 to 0.5 μm. In addition, the number average molecular weight (Mn) of the sodium salt of polyurethane is not particularly limited, and may be, for example, 10,000 or more, or 50,000 or more.
[0058] [Binder composition for electrode]
[0059] The electrode adhesive composition of the lithium secondary battery of the present embodiment comprises a sodium salt of polyurethane obtained by reacting the above-mentioned components (A) to (D), a conductive agent and water. In detail, the electrode adhesive composition comprises the sodium salt of the above-mentioned polyurethane and the conductive agent in a state dispersed in water. The electrode adhesive composition can also be prepared, for example, by mixing an aqueous dispersion of the sodium salt of the above-mentioned polyurethane with an aqueous dispersion of the conductive agent.
[0060] As a conductive agent, an electronic conductive material that does not adversely affect battery performance can be used. As a specific example of a conductive agent, carbon black such as fibrous nanocarbon, acetylene black, Ketjen black, natural graphite (scaly graphite, flaky graphite, earthy graphite, etc.), artificial graphite, carbon whisker, carbon fiber, metal (copper, nickel, aluminum, silver, gold, etc.) powder, metal fiber, conductive ceramic material and other conductive materials can be cited. They can use any one or two or more in combination.
[0061] As the conductive agent, fibrous nanocarbon is preferably used. Fibrous nanocarbon can follow the electrode expansion when the electrode active material contains SiO, and can suppress the damage of the conductive path during repeated charge and discharge.
[0062] Fibrous nanocarbon is a fibrous carbon having a nanoscale fiber diameter. The average fiber length of the fibrous nanocarbon is not particularly limited, for example, preferably 50nm to 10mm, more preferably 0.5μm to 100μm. The average fiber diameter of the fibrous nanocarbon is not particularly limited, for example, preferably 0.5nm to 200nm, more preferably 1nm to 100nm. The average fiber length and the average fiber diameter can be obtained by measuring the size of 50 randomly selected fibrous nanocarbons in an atomic force microscope (AFM) image and taking the arithmetic average. For the mm-level length that cannot be measured by atomic force microscopy, the image based on the microscope can be used for measurement.
[0063] Specific examples of fibrous nanocarbons include single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), and carbon nanofibers. Any one of these or any two or more of these may be used in combination. Among these, carbon nanotubes are preferred, and SWCNTs are more preferred.
[0064] The binder composition of one embodiment preferably contains the sodium salt of polyurethane (X) and fibrous nanocarbon (Y) in a ratio of (X):(Y)=60:40 to 99.6:0.4 (mass ratio). This can enhance the effect of improving the charge and discharge cycle characteristics of the lithium secondary battery.
[0065] The binder composition of one embodiment preferably contains fibrous nanocarbon and carbon black as a conductive agent. In this case, carbon black is used as a conductive aid to be responsible for the conduction around the electrode active material, and the conductivity of the fibrous nanocarbon that follows the expansion of the electrode can be more effectively exerted. The content ratio of fibrous nanocarbon to carbon black is not particularly limited, for example, relative to 100 parts by mass of fibrous nanocarbon, the carbon black can be 100 to 2000 parts by mass.
[0066] The conductive agent is preferably used in a state dispersed in a medium. As the medium, water is generally used, but polar organic solvents such as alcohols and ketone solvents, or mixed solvents of these polar organic solvents and water may also be used. As a dispersing device for dispersing the conductive agent in the medium, for example, a jet mill, a high-pressure dispersing device, an ultrasonic homogenizer, etc. may be cited.
[0067] When preparing the aqueous dispersion formed by dispersing the conductive agents such as fibrous nanocarbon and carbon black in water, a dispersant can be added. As a dispersant, for example, celluloses such as hydroxymethyl cellulose, carboxymethyl cellulose and its alkali metal salt, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, cellulose nanofibers, polyacrylic acid, sodium polyacrylate and other polycarboxylic acid compounds, polyvinyl pyrrolidone and other compounds with vinyl pyrrolidone structure, polyvinyl alcohol, sodium alginate, xanthan gum, carrageenan, guar gum, agar, starch, etc. can be listed. Among them, preferably carboxymethyl cellulose salt is used.
[0068] In the electrode binder composition, the concentration of the polyurethane is not particularly limited, and may be, for example, 5% to 50% by mass, or 10% to 40% by mass. The concentration of the conductive agent is also not particularly limited, and may be, for example, 5% to 35% by mass, or 15% to 30% by mass.
[0069] [Electrode coating liquid composition]
[0070] The electrode binder and electrode binder composition of the present embodiment are used to prepare an electrode coating liquid composition for manufacturing an electrode of a lithium secondary battery. When an electrode binder is used, the electrode coating liquid composition (1) comprises an electrode binder, an electrode active material and a conductive agent. When an electrode binder composition is used, the electrode coating liquid composition (2) comprises an electrode binder composition and an electrode active material.
[0071] These electrode coating liquid compositions are preferably used to manufacture the negative electrode of lithium secondary battery. Therefore, the electrode active material is preferably a negative electrode active material. As the negative electrode active material, a substance capable of embedding / de-embedding metallic lithium or lithium ions can be used. As a specific example of the negative electrode active material, carbon materials such as natural graphite, artificial graphite, difficult graphitized carbon, easy graphitized carbon, metallic materials such as metallic lithium, alloys, tin compounds, lithium transition metal nitrides, crystalline metal oxides, amorphous metal oxides, silicon compounds, conductive polymers, etc. can be cited. Any one of them can be used, or two or more can be used in combination.
[0072] Among them, the negative electrode active material preferably contains SiO (silicon monoxide) because it can achieve a high capacity. The negative electrode active material may be a mixture of SiO and graphite, but it is preferred to use only SiO as the negative electrode active material.
[0073] The content of the sodium salt of polyurethane in the electrode coating composition is not particularly limited, but is preferably 1 to 20% by mass, more preferably 2 to 13% by mass, relative to the content of the electrode active material (negative electrode active material).
[0074] In the above-mentioned electrode coating liquid composition (1), the conductive agent includes specific examples and preferred compositions, and the electrode binder composition is as described above, and the description thereof is omitted.
[0075] The content of the conductive agent in the electrode coating composition is not particularly limited, but is preferably 0.1 to 20% by mass, more preferably 0.2 to 10% by mass, relative to the content of the electrode active material (negative electrode active material).
[0076] The electrode coating liquid composition may include a thickener such as a water-soluble polymer as a viscosity regulator for slurrying the composition. As a thickener, for example, celluloses such as carboxymethyl cellulose salts, methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, polycarboxylic acid compounds such as polyacrylic acid, sodium polyacrylate, compounds with a vinyl pyrrolidone structure such as polyvinyl pyrrolidone, polyacrylamide, polyethylene oxide, polyvinyl alcohol, sodium alginate, xanthan gum, carrageenan, guar gum, agar, starch, etc. can be cited. They can use any one or a combination of two or more. Among them, carboxymethyl cellulose salts are preferred.
[0077] The content of the electrode active material (negative electrode active material) in the solid content of the electrode coating liquid composition is not particularly limited, and may be, for example, 65% to 99% by mass, or 75% to 97% by mass. The content of the dispersion medium such as water in the electrode coating liquid composition is not particularly limited, and may be, for example, 20% to 80% by mass, or 40% to 70% by mass.
[0078] The method for preparing the electrode coating composition is not particularly limited. When mixing the above components, for example, a mortar, a grinder, a ball mill such as a planetary ball mill or a vibration ball mill, mechanical fusion, etc. can be used.
[0079] [Negative electrode of lithium secondary battery]
[0080] The negative electrode of the lithium secondary battery of the embodiment can be manufactured by applying the above-mentioned electrode coating liquid composition to the collector and evaporating the dispersion medium. That is, the negative electrode has a collector and a negative electrode mixture layer (also referred to as an active material layer) formed on the collector, and the negative electrode mixture layer is formed by the solid material of the above-mentioned electrode coating liquid composition. In one embodiment, the electrode coating liquid composition includes the above-mentioned electrode binder or electrode binder composition, and SiO as a negative electrode active material. Therefore, the negative electrode of the lithium secondary battery of one embodiment includes: a solid component of an electrode binder or an electrode binder composition and a negative electrode active material containing SiO.
[0081] As the current collector, an electron conductor that does not have adverse effects in the constructed battery can be used. As the current collector for the negative electrode, for example, in addition to copper, stainless steel, nickel, aluminum, titanium, calcined carbon, conductive polymers, conductive glass, Al-Cd alloy, etc., for the purpose of improving adhesion, conductivity, and oxidation resistance, a current collector obtained by treating the surface of copper, etc. with carbon, nickel, titanium, silver, etc. can also be cited. The surface of these collector materials can be oxidized. As the shape of the collector, for example, a foil, a film, a sheet, a mesh, a punched or drawn object, a lath body, a porous body, a foam body and the like can be cited. The thickness of the collector is not particularly limited, and a collector of 1μm to 100μm is usually used.
[0082] The thickness of the negative electrode mixture layer is not particularly limited, and may be, for example, 15 μm to 150 μm.
[0083] [Lithium secondary battery]
[0084] The lithium secondary battery involved in the embodiment has the above-mentioned negative electrode. In detail, the lithium secondary battery has a negative electrode, a positive electrode, a separator disposed between the negative electrode and the positive electrode, and an electrolyte, and the negative electrode uses an electrode made using the above-mentioned electrode coating liquid composition. Regarding the positive electrode, the separator and the electrolyte, for example, the known structure described in the above-mentioned patent document 1 or patent document 2 can be adopted, without particular limitation.
[0085] The lithium secondary battery involved in the embodiment can be formed into a cylindrical, coin-shaped, square, or any other shape. The basic structure of the battery is the same, regardless of the shape, and can be implemented by design changes according to the purpose. For example, in the case of a cylindrical shape, a winding body formed by winding a negative electrode formed by coating a negative electrode active material on a negative electrode collector and a positive electrode formed by coating a positive electrode active material on a positive electrode collector through a diaphragm is stored in a battery can, a non-aqueous electrolyte is injected, and the insulating plate is placed on top and bottom to seal. In addition, in the case of a coin-type lithium secondary battery, a disc-shaped negative electrode, a diaphragm, a disc-shaped positive electrode, and a stainless steel plate are stored in a coin-type battery can in a stacked state, and a non-aqueous electrolyte is injected and sealed.
[0086] Example
[0087] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples, but the present invention is not limited thereto.
[0088] The details of the polyol, fibrous nanocarbon aqueous dispersion 1, fibrous nanocarbon aqueous dispersion 2, acetylene black aqueous dispersion, and carboxymethyl cellulose sodium salt used in the examples are as follows.
[0089] Hydrogenated polybutadiene polyol (A1): "NISSO-PB GI-1000" manufactured by Nippon Soda Co., Ltd. (Mn: 1500, iodine value 11 g / 100 g, hydroxyl value 69 KOH mg / g, number of functional groups: 1.8)
[0090] Hydrogenated polybutadiene polyol (A2): "NISSO-PB GI-3000" manufactured by Nippon Soda Co., Ltd. (Mn: 3100, iodine value 12 g / 100 g, hydroxyl value 30 KOHmg / g, number of functional groups: 1.7)
[0091] Polybutadiene polyol: "NISSO-PB G-1000" manufactured by Nippon Soda Co., Ltd. (Mn: 1400, hydroxyl value 70 KOHmg / g, number of functional groups: 1.7)
[0092] · Polyisoprene polyol: "Polyip" manufactured by Idemitsu Kosan Co., Ltd. (Mn: 2500, hydroxyl value 47 KOHmg / g, number of functional groups: 2.1)
[0093] · Fibrous nanocarbon aqueous dispersion 1: Using "TUBALL BATT" (CNT purity> 93%, average diameter 1.6±0.5 nm) manufactured by OCSiAl as single-walled carbon nanotubes (SWCNT), a fibrous nanocarbon aqueous dispersion 1 having a fibrous nanocarbon concentration of 1% by mass was prepared by the following manufacturing steps. The average fiber diameter, average fiber length, and aspect ratio of the fibrous nanocarbon were measured for the obtained aqueous dispersion 1 by the following measurement method, and the results showed that the average fiber diameter was 3 nm, the average fiber length was 3000 nm, and the aspect ratio was 1000.
[0094] (Process for producing fibrous nanocarbon aqueous dispersion)
[0095] 0.5 g of SWCNT was mixed in a beaker with 50 g of a 1% aqueous solution of carboxymethyl cellulose salt ("Celogen 7A" manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.), and after stirring, the slurry was circulated and dispersed at an output power of 100 μA for 90 minutes using a beaker, an ultrasonic homogenizer (US-600T manufactured by Nippon Seiki Seisaku-sho Co., Ltd.), a circulation unit and a tube pump to obtain a fibrous nanocarbon aqueous dispersion.
[0096] (Measurement method of fibrous nanocarbon)
[0097] The average fiber diameter and average fiber length of fibrous nanocarbon are measured using a scanning probe microscope (SPM) (manufactured by JEOL Ltd., AFM-5300E). That is, the fibrous nanocarbon aqueous dispersion is diluted with water to a concentration of fibrous nanocarbon of 0.01 mass %, and then unfolded on a mica substrate to evaporate the solvent. Then, the AFM image of the sample is observed, and the average fiber diameter and average fiber length are calculated according to the method described above. In addition, using these values, the aspect ratio is calculated according to the following (Formula 1).
[0098] Aspect ratio = average fiber length (nm) / average fiber diameter (nm) (Formula 1)
[0099] Fibrous nanocarbon aqueous dispersion 2: Using "HCNT2" (CNT purity> 96%, average diameter 1nm to 4nm) manufactured by SUSN NANOTECH as single-walled carbon nanotubes (SWCNT), a fibrous nanocarbon aqueous dispersion 2 having a fibrous nanocarbon concentration of 1% by mass was prepared by the same manufacturing steps as the above aqueous dispersion 1. The average fiber diameter, average fiber length, and aspect ratio of the fibrous nanocarbon were measured for the obtained aqueous dispersion 2 by the above-mentioned measurement method, and the results showed that the average fiber diameter was 3nm, the average fiber length was 35000nm, and the aspect ratio was 11666.
[0100] Acetylene black water dispersion: "Li400" manufactured by Denka Co., Ltd. was used as acetylene black. 100 g of acetylene black was added to 300 g of a 1% by mass aqueous solution of carboxymethyl cellulose salt ("Celogen 7A" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) while stirring with a high-speed disperser, and stirred until uniform. Thus, an acetylene black water dispersion having an acetylene black concentration of 25% by mass was obtained.
[0101] · Carboxymethylcellulose sodium salt: "Serogen BSH-6" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.
[0102] [Synthesis of polyurethane aqueous dispersion]
[0103] (Manufacturing Example 1: Adhesive 1)
[0104] In a four-necked flask equipped with a stirrer, a reflux cooling tube, a thermometer, and a nitrogen blowing tube, 69.17 parts by mass of hydrogenated polybutadiene polyol (A1), 4.17 parts by mass of dimethylol propionic acid, 25.97 parts by mass of dicyclohexylmethane 4,4'-diisocyanate (hydrogenated MDI), and 150 parts by mass of methyl ethyl ketone were added, and the mixture was reacted at 75°C for 4 hours to obtain a methyl ethyl ketone solution of a urethane prepolymer having a free isocyanate group content of 2.1% by mass relative to the non-volatile component. The solution was cooled to 45°C, and an aqueous sodium hydroxide solution containing 1.24 parts by mass of sodium hydroxide and 233 parts by mass of water was slowly added, and the mixture was emulsified and dispersed using a homogenizer. Next, an aqueous solution prepared by diluting 1.48 parts by mass of diethylenetriamine with 37 parts by mass of water was added, and a chain extension reaction was performed for 1 hour. The solvent was removed under reduced pressure and heating at 50° C. to obtain an aqueous dispersion of a sodium salt of polyurethane having a nonvolatile content of about 32% by mass (adhesive 1).
[0105] (Manufacturing Example 2: Adhesive 2)
[0106] An aqueous dispersion of a sodium salt of polyurethane having a nonvolatile content of approximately 32% by mass (adhesive 2) was obtained in the same manner as in Production Example 1 except that 25.97 parts by mass of isophorone diisocyanate (IPDI) was used in place of 25.97 parts by mass of hydrogenated MDI and the amount of diethylenetriamine was changed to 2.57 parts by mass.
[0107] (Manufacturing Example 3: Adhesive 3)
[0108] An aqueous dispersion of a sodium salt of polyurethane having a nonvolatile content of approximately 32% by mass (adhesive 3) was obtained in the same manner as in Production Example 1 except that 25.97 parts by mass of hexamethylene diisocyanate (HDI) was used instead of 25.97 parts by mass of hydrogenated MDI and the amount of diethylenetriamine was changed to 4.9 parts by mass.
[0109] (Manufacturing Example 4: Adhesive 4)
[0110] An aqueous dispersion of a sodium salt of polyurethane having a nonvolatile content of approximately 32% by mass (adhesive 4) was obtained in the same manner as in Production Example 1, except that 69.17 parts by mass of hydrogenated polybutadiene polyol (A2) was used instead of 69.17 parts by mass of hydrogenated polybutadiene polyol (A1) and that the amount of diethylenetriamine was changed to 2.94 parts by mass.
[0111] (Manufacturing Example 5: Adhesive 5)
[0112] An aqueous dispersion of a sodium salt of polyurethane having a nonvolatile content of approximately 32% by mass (adhesive 5) was obtained in the same manner as in Production Example 1, except that 4.17 parts by mass of dimethylolbutyric acid was used instead of 4.17 parts by mass of dimethylolpropionic acid, and the amount of hydrogenated polybutadiene polyol (A1) was 69.22 parts by mass, the amount of hydrogenated MDI was 25.99 parts by mass, the amount of sodium hydroxide was 1.13 parts by mass, and the amount of diethylenetriamine was 2.26 parts by mass.
[0113] (Manufacturing Example 6: Adhesive 6)
[0114] An aqueous dispersion of a sodium salt of polyurethane having a nonvolatile content of about 32% by mass (Binder 6) was obtained in the same manner as in Production Example 1 except that 1.29 parts by mass of ethylenediamine was used instead of 1.48 parts by mass of diethylenetriamine.
[0115] (Manufacturing Example 7: Adhesive 7)
[0116] The same operation as in Production Example 1 was carried out except that the amount of hydrogenated polybutadiene polyol (A1) was set to 66.97 parts by mass, the amount of dimethylolpropionic acid was set to 6.14 parts by mass, the amount of hydrogenated MDI was set to 25.89 parts by mass, the amount of sodium hydroxide was set to 1.83 parts by mass, and the amount of diethylenetriamine was set to 0.63 parts by mass, to obtain an aqueous dispersion of a sodium salt of polyurethane having a non-volatile content of approximately 32% by mass (adhesive 7).
[0117] (Manufacturing Example 8: Adhesive 8)
[0118] The same operation as in Production Example 1 was carried out except that the amount of hydrogenated polybutadiene polyol (A1) was set to 71.39 parts by mass, the amount of dimethylolpropionic acid was set to 2.19 parts by mass, the amount of hydrogenated MDI was set to 26.06 parts by mass, the amount of sodium hydroxide was set to 0.65 parts by mass, and the amount of diethylenetriamine was set to 2.32 parts by mass, to obtain an aqueous dispersion of a sodium salt of polyurethane having a non-volatile content of approximately 32% by mass (adhesive 8).
[0119] (Comparative Production Example 1: Adhesive C1)
[0120] An aqueous dispersion of a sodium salt of polyurethane having a nonvolatile content of approximately 32% by mass (Binder C1) was obtained in the same manner as in Production Example 1, except that 69.76 parts by mass of polybutadiene polyol was used instead of 69.17 parts by mass of hydrogenated polybutadiene polyol (A1), and the amount of hydrogenated MDI was set to 25.47 parts by mass, the amount of dimethylolpropionic acid was set to 4.10 parts by mass, the amount of sodium hydroxide was set to 1.22 parts by mass, and the amount of diethylenetriamine was set to 1.28 parts by mass.
[0121] (Comparative Production Example 2: Adhesive C2)
[0122] An aqueous dispersion of an ammonium salt of a polyurethane having a nonvolatile content of approximately 32% by mass (adhesive C2) was obtained in the same manner as in Production Example 1, except that 2.12 parts by mass of a 25% by mass aqueous ammonia solution was used instead of 1.24 parts by mass of sodium hydroxide, and the amount of hydrogenated polybutadiene polyol (A1) was set to 69.28 parts by mass and the amount of hydrogenated MDI was set to 26.01 parts by mass.
[0123] (Comparative Production Example 3: Adhesive C3)
[0124] An aqueous dispersion of a potassium salt of a polyurethane having a nonvolatile content of approximately 32% by mass was obtained in the same manner as in Production Example 1, except that 4.24 parts by mass of dimethylolbutyric acid was used instead of 4.17 parts by mass of dimethylolpropionic acid, 1.61 parts by mass of potassium hydroxide was used instead of 1.24 parts by mass of sodium hydroxide, and the amount of hydrogenated polybutadiene polyol (A1) was set to 68.83 parts by mass, the amount of hydrogenated MDI was set to 25.84 parts by mass, and the amount of diethylenetriamine was set to 1.47 parts by mass.
[0125] (Comparative Production Example 4: Adhesive C4)
[0126] An aqueous dispersion of a potassium salt of a polyurethane having a nonvolatile content of approximately 32% by mass (binder C4) was obtained in the same manner as in Production Example 1, except that 1.74 parts by mass of potassium hydroxide was used instead of 1.24 parts by mass of sodium hydroxide, and the amount of hydrogenated polybutadiene polyol (A1) was set to 68.83 parts by mass, the amount of hydrogenated MDI was set to 25.84 parts by mass, the amount of dimethylolpropionic acid was set to 4.15 parts by mass, and the amount of diethylenetriamine was set to 1.47 parts by mass.
[0127] (Comparative Production Example 5: Adhesive C5)
[0128] An aqueous dispersion of a triethylamine salt of a polyurethane having a nonvolatile content of approximately 32% by mass (adhesive C5) was obtained in the same manner as in Production Example 1, except that 3.07 parts by mass of triethylamine was used instead of 1.24 parts by mass of sodium hydroxide, and the amount of hydrogenated polybutadiene polyol (A1) was set to 67.51 parts by mass, the amount of hydrogenated MDI was set to 25.35 parts by mass, the amount of dimethylolpropionic acid was set to 4.07 parts by mass, and the amount of diethylenetriamine was set to 1.44 parts by mass.
[0129] (Comparative Production Example 6: Adhesive C6)
[0130] An aqueous dispersion of a sodium salt of polyurethane having a nonvolatile content of approximately 32% by mass (Binder C6) was obtained in the same manner as in Production Example 1 except that 69.17 parts by mass of polyisoprene polyol was used instead of 69.17 parts by mass of hydrogenated polybutadiene polyol (A1) and that the amount of diethylenetriamine was changed to 2.31 parts by mass.
[0131] [Evaluation of polyurethane aqueous dispersion]
[0132] Regarding the obtained adhesives 1 to 8 and adhesives C1 to C6, the constituent components of the polyurethane are shown in Table 1. In Table 1, the carboxylic acid of the component (C) is shown with the compound name and content in the salt after neutralization. In addition, for adhesives 1 to 8 and adhesives C1 to C6, the acid value of the polyurethane and the average particle size of the polyurethane aqueous dispersion were measured. The measurement method is as follows.
[0133] ·Acid value of polyurethane: measured in accordance with JIS K0070-1992.
[0134] Average particle size of polyurethane aqueous dispersion: The particle size at 50% accumulation, d50 (median particle size), was measured using "Microtrac UPA-UZ152" manufactured by Nikkiso Co., Ltd.
[0135] [Table 1]
[0136]
[0137] [Manufacturing of lithium secondary batteries]
[0138] (Example 1)
[0139] (Preparation of Negative Electrode) 88.85 parts by mass of SiO (average particle size 4.5 μm, specific surface area 5.5 m) was used as the negative electrode active material. 2 / g), 40 parts by mass of fibrous nanocarbon aqueous dispersion 1 and 4.0 parts by mass of acetylene black aqueous dispersion as a conductive agent, 43.3 parts by mass of a 1.5% aqueous solution of carboxymethyl cellulose sodium salt as a thickener, and 30 parts by mass of an aqueous dispersion of polyurethane sodium salt as a binder 1, 14 parts by mass of ion exchange water, are mixed with a planetary mixer to prepare a negative electrode slurry in a manner such that the solid content reaches 49% by mass. An electrolytic copper foil with a thickness of 10 μm is used as a current collector, and a negative electrode mixture layer containing the above-mentioned negative electrode slurry is formed on the electrolytic copper foil. In detail, the above-mentioned negative electrode slurry is applied to the electrolytic copper foil with a coater, and after roller pressing, it is dried under reduced pressure at 130°C to obtain 2.7 mg / cm of negative electrode active material. 2 of the negative electrode.
[0140] (Production of positive electrode)
[0141] 92 parts by mass of LiNiCoAlO2 (NCA) as a positive electrode active material, 4 parts by mass of acetylene black ("Li-400" manufactured by Denka (Strain) as a conductive agent, 4 parts by mass of polyvinylidene fluoride as a binder, and 49.2 parts by mass of N-methyl-2-pyrrolidone as a dispersion medium were mixed with a planetary mixer to prepare a positive electrode slurry with a solid content of 67% by mass. The positive electrode slurry was coated on an aluminum foil with a thickness of 15 μm with a coating machine, dried at 130°C, and then roller pressed to obtain a positive electrode active material of 16.6 mg / cm 2 The positive electrode.
[0142] (Battery production)
[0143] The negative electrode and positive electrode obtained above were combined, and a polyolefin-based (PE / PP / PE) separator was sandwiched between the electrodes for stacking. The positive terminal and the negative terminal were ultrasonically welded on each positive and negative electrode. The stack was placed in an aluminum laminate packaging material, and the opening for liquid injection was retained and heat-sealed. The positive electrode area was 18 cm 2 , the negative electrode area is 19.8cm 2 Next, an electrolyte solution prepared by dissolving LiPF6 (1.0 mol / L) in a solvent mixed with ethylene carbonate and diethyl carbonate (30 / 70 volume ratio) was injected, and the opening was heat-sealed to obtain an evaluation battery.
[0144] (Example 2 to Example 8 and Comparative Example 1 to Comparative Example 6)
[0145] A negative electrode was produced in the same manner as in Example 1 except that binders 2 to 8 and C1 to C6 described in Table 2 below were used as binders when preparing the negative electrode slurry, and further a battery for evaluation was produced.
[0146] (Example 9)
[0147] A negative electrode was produced in the same manner as in Example 1 except that 40 parts by mass of the fibrous nanocarbon aqueous dispersion 2 and 4 parts by mass of the acetylene black aqueous dispersion were used as conductive agents when preparing the negative electrode slurry, and further a battery for evaluation was produced.
[0148] [evaluate]
[0149] The adhesiveness of the produced negative electrode was evaluated. In addition, for the evaluation battery, in order to confirm the effect of reducing electrode expansion, the electrode expansion rate (first time) and the electrode expansion rate (second time) after charge and discharge were measured. In addition, for the evaluation battery, the presence or absence of gas generation, battery impedance and charge and discharge cycle characteristics were measured and evaluated. The test method is as follows.
[0150] (Adhesion)
[0151] Cut the negative electrode into 3×6 cm, bend it 180° so that the coating surface faces inward to form 3×3 cm, and after restoration, visually judge the degree of shedding of the active material on the coating surface (the length of the shedding part relative to the bending part). The evaluation criteria are as follows.
[0152] Evaluation criteria:
[0153] 5 points: 0% shedding (no shedding)
[0154] 4 points: shedding less than 5% (very few electrolytic copper foils visible)
[0155] 3 points: shedding more than 5% and less than 25%
[0156] 2 points: shedding more than 25% and less than 50%
[0157] 1 point: shedding more than 50% (there is also shedding from the peripheral part of the bend)
[0158] (Electrode expansion rate)
[0159] Measure the thickness of the negative electrode when assembling the evaluation battery, the thickness of the battery before charging (the thickness of the battery before charging (Japanese: セル厚み)), and the thickness of the battery after each charge and discharge (the thickness of the battery after each evaluation) with a micrometer, and calculate using the following formula.
[0160] Electrode expansion rate = (thickness of the battery after each evaluation - thickness of the battery before charging) / thickness of the negative electrode binder layer × 100%
[0161] Thickness of the negative electrode binder layer = thickness of the negative electrode - thickness of the copper foil
[0162] The charge and discharge conditions are as described below, and the electrode expansion rate is measured after the first charge and discharge and the second charge and discharge.
[0163] Charge and discharge conditions: Charge with a constant current (CC) at a current density equivalent to 0.2C until 4.2V, then switch to constant voltage (CV) charging at 4.2V and charge until a current density equivalent to 0.02C. Discharge with a constant current (CC) at a current density equivalent to 0.2C until 2.7V.
[0164] (Gas generation)
[0165] Charge the evaluation battery for the first time under the same charging conditions as the above measurement of the electrode expansion rate, then open it and perform a decompression seal. Consider the case where an amine odor that is not the odor of the electrolyte (Japanese: 臭気) is felt as gas generation, and consider the case where no amine odor is felt as no gas generation.
[0166] (Battery impedance)
[0167] For the evaluation battery initially charged under the same charging conditions as in the above electrode expansion rate measurement, the battery impedance (mΩ) at a frequency of 1 kHz was measured using an AC milliohm tester ("3560" manufactured by Hioki Electric Co., Ltd.).
[0168] (Charge and discharge cycle characteristics)
[0169] For the evaluation battery, a charge and discharge cycle test was performed using a charge and discharge device under the following conditions. CC (constant current) charging was performed at a current density equivalent to 1C until 4.2V, then switched to CV (constant voltage) charging at 4.2V, charging for 1.5 hours or until the current density reached 0.1C, then CC discharge was performed at a current density equivalent to 1C until 2.7V, and the cycle was performed 200 times at 20°C, and the ratio of the 1C discharge capacity after 200 times to the initial 1C discharge capacity was calculated as the charge and discharge cycle retention rate (%). The rest period between charging and discharging was set to 10 minutes.
[0170] [Table 2]
[0171]
[0172] The results are shown in Table 2. In Comparative Example 1 using an aqueous dispersion of polyurethane synthesized using non-hydrogenated polybutadiene polyol as a binder, the expansion rate of the negative electrode during charge and discharge was high. In addition, in Comparative Example 1, the binding property of the binder in the negative electrode was poor. In Comparative Example 6 using an aqueous dispersion of polyurethane synthesized using isoprene polyol as a binder, the expansion rate of the negative electrode during charge and discharge was also high.
[0173] In Comparative Examples 2 to 5, the polyurethane used as the binder was not a sodium salt but a potassium salt or an amine salt, so the expansion rate of the negative electrode during charge and discharge was high. In addition, in Comparative Examples 2 and 5 where the polyurethane was an amine salt, gas was generated during charge and discharge, and odor was confirmed. In Comparative Examples 3 and 4 where the polyurethane was a potassium salt, the adhesiveness of the binder was poor.
[0174] In contrast, in Examples 1 to 9, the adhesiveness of the binder is excellent, and the electrode expansion rate (first time) and the electrode expansion rate (second time) after charge and discharge are low compared to Comparative Example 1, and the expansion of the negative electrode caused by charge and discharge can be reduced. In addition, no gas is generated during charge and discharge, and the battery impedance is small, and the charge and discharge cycle characteristics are also excellent.
[0175] It should be noted that the various numerical ranges described in the specification can be arbitrarily combined with their upper and lower limits, and all of these combinations are described in the specification as preferred numerical ranges. In addition, the description of the numerical range of "X to Y" means greater than X and less than Y.
[0176] Several embodiments of the present invention are described above, but these embodiments are given as examples only and are not intended to limit the scope of the invention. These embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the subject matter of the invention. These embodiments or their omissions, substitutions, and changes are included in the scope and subject matter of the invention, and are also included in the invention described in the claims and their equivalents.
Claims
1. A binder for electrodes of lithium secondary batteries, characterized in that: An aqueous dispersion containing a sodium salt of a polyurethane obtained by reacting (A) at least one of an aliphatic polyisocyanate and an alicyclic polyisocyanate, (B) a hydrogenated polybutadiene polyol, (C) a carboxylic acid having one or more active hydrogen groups, and (D) a chain extender.
2. The electrode binder according to claim 1, wherein The electrode binder is used for a negative electrode of a lithium secondary battery, and the negative electrode contains SiO as a negative electrode active material.
3. A binder composition for an electrode of a lithium secondary battery, comprising: A sodium salt of a polyurethane obtained by reacting (A) at least one of an aliphatic polyisocyanate and an alicyclic polyisocyanate, (B) a hydrogenated polybutadiene polyol, (C) a carboxylic acid having one or more active hydrogen groups, and (D) a chain extender; Conductive agent; and water.
4. The binder composition for an electrode according to claim 3, wherein The conductive agent includes fibrous nanocarbon.
5. A negative electrode of a lithium secondary battery, characterized in that: Include: The solid content of the electrode binder according to claim 1 or the electrode binder composition according to claim 3; and A negative electrode active material containing SiO.
6. The negative electrode according to claim 5, wherein The negative electrode includes fibrous nanocarbon as a conductive agent.
7. A lithium secondary battery, characterized in that: A negative electrode according to claim 5 is provided.
Citation Information
Patent Citations
Binder for electrode in lithium secondary cell, electrode manufactured using said binder, and lithium secondary cell in which said electrode is used
WO2015019598A1
Binder composition for electrode, coating composition for electrode, electrode for power storage device, and power storage device
WO2020217730A1